Definition and Neurophysiological Structure of Attention - Coşkun, Nilgün (Lut TAMAM, 2026)
This study attempts to define the subject of attention, which is at the forefront of cognitive skills that are required for daily life. This review aims to determine attention and understand its neurophysiological structure, as well as to elucidate the distinctions in terms of orientation, detection, and alertness functions in more detail. In addition, along with the explanation of attention-related disorders and their symptoms, suggestions that can be used in treatment and rehabilitation processes have been presented, and an individual, social, and technological perspective has been provided for the studies to be carried out in the future. Attention, defined in the simplest sense as the ability to focus on a location, object, or message, is a cognitive process necessary for cognitive functions such as perception, learning, memory, decision-making, and reasoning skills. The subfunctions of attention, orientation, detection, and alertness have been defined. Cortex areas related to attention and different aspects of attention have been reviewed, supported by neuropsychological study findings related to attention. Based on the findings obtained from the studies, evidence indicates that attention has a neurophysiological structure that spreads over very different areas of the brain. In particular, an increase in parietal cortex activity in tasks related to attention is among the common findings of the studies. In addition, functional differences have been revealed between the right and left hemispheres during attention processing. In addition, studies on developmental, neurocognitive, and mood disorders in which attention function is impaired have been reviewed.

Bu çalışmada günlük yaşam için gerekli bilişsel becerilerin başında gelen dikkat konusunun tanımı yapılmaya çalışılmıştır. Derlemenin amacı dikkatin tanımının yapılması ve nörofizyolojik yapısının anlaşılması yanında; yönelim, farkındalık ve alarma geçme işlevleri açısından ayrışmanın daha detaylı ortaya konulmasıdır. Bunun yanında dikkat ile ilişkili bozuklukların ve belirtilerinin açıklanması ile beraber, tedavi ve rehabilitasyon süreçlerinde kullanılabilecek öneriler sunulmuş, ilerleyen dönemlerde yapılacak çalışmalara bireysel, sosyal ve teknolojik bir bakış açısı sağlanmaya çalışılmıştır. En basit anlamda bir konuma, nesneye ya da mesaja odaklanma becerisi olarak tanımlanan dikkat; algı, öğrenme, bellek, karar verme, muhakeme yapma becerileri gibi bilişsel işlevler için gerekli bir süreçtir. Dikkatin alt işlevleri olan yönelim, farkındalık ve alarma geçme işlevleri tanımlanmıştır. Dikkat ile ilişkili nöropsikolojik çalışma bulgularıyla desteklenerek dikkat ve dikkatin farklı yönleriyle ilişkili korteks alanları derlenmiştir. Çalışmalardan elde edilen bulgulara dayanarak dikkatin beynin çok farklı alanlarına yayılmış bir nörofizyolojik yapısı olduğu kanıtlanmıştır. Özellikle dikkat ile ilişkili görevlerde parietal korteks aktivitesindeki artış çalışmaların ortak bulguları arasındadır. Ayrıca dikkatin işlenmesi konusunda sağ ve sol hemisfer arasında fonksiyonel farklılıklar ortaya konmuştur. Bunun yanında dikkat işlevinin bozulduğu gelişimsel, nörokognitif ve duygudurum bozukluklarına ilişkin çalışmalar derlenmiştir.
Dikkatin Tanımı ve Nörofizyolojik Yapısı
Keywords: Memory and Attention; Hafıza ve Dikkat